Study on Safety Management Assessment of Coal Mine Roofs Based on the DEMATEL-ANP Method - Li, Lei; Ouyang, Youpeng (Frontiers in Earth Science, 2022)
Coal mine roof accident are one of the main single risks faced by coal miners. According to the statistical data of coal mine accidents in China, there were 40 roof accidents and 55 deaths in 2020 alone, accounting for 32.8% and 24.4% of the total respectively. Therefore, we can see its danger. In order to realize the comprehensive scientific assessment of coal mine roof accident, firstly, through the collation and analysis of relevant literature review and accident investigation reports, combined with the expert investigation method, the assessment index system of coal mine roof accidents is constructed; Then, based on the analysis of the characteristics of influencing factors of coal mine roof accident, the assessment model of coal mine roof accident is established by using DEMATEL-ANP method; Finally, the established assessment model is applied to a coal mine to verify the rationality of the model.